MEASUREMENTS OF NEUTRON CAPTURE EFFECTS ON CD, SM AND GD IN LUNAR SAMPLES WITH IMPLICATIONS FOR THE NEUTRON ENERGY SPECTRUM - Sands D.G.; De Laeter J.R.; Rosman K.J.R. (My University, 2001)
The bombardment of the lunar surface by cosmic rays produces secondary neutrons, some of which are thermalized by the lunar soil and then interact strongly with the isotopes of Cd, Gd and Sm which have high neutron capture cross sections at thermal energies causing changes in their isotopic compositions. We have measured these changes in samples from the Apollo 14, 16 and 17 missions using thermal ionization mass spectrometry. Changes of 114Cd/113Cd of 0.3-0.5% in samples 60501,105, 65701,23 and 72161,73, of 0.4 and 0.8% in 158Gd/157Gd in samples 14163,848 and 60501,105 and of 0.8, 1.2 and 0.06% for 150Sm/149Sm in samples 14163,848 and 60501,105 and 74220,125 respectively, have been observed. This is the first time that neutron capture on Cd has been detected in lunar samples. Thermal neutrons are captured preferentially at resonance energies of 0.03 eV by 155Gd and 157Gd, at 0.09 eV by 149Sm and at 0.178 eV by 113Cd. A comparison of the changes in 114Cd/113Cd, 156Gd/155Gd, 158Gd/157Gd and 150Sm/149Sm due to neutron capture can therefore indicate the energy distribution of the neutrons. Previous work has compared changes in 158Gd/157Gd and 150Sm/149Sm, while this study extends the comparison to 114Cd/113Cd, where the resonance energy is significantly higher. This has enabled us to confirm evidence for a harder neutron energy spectrum in lunar soil than is predicted theoretically. This can be seen in significantly higher capture rates than predicted for 149Sm compared to 157Gd. We also present evidence of enhanced capture rates on 113Cd compared with 149Sm and 157Gd. The concentrations of Cd, Gd and Sm in nine lunar samples have also been measured by isotope dilution mass spectrometry with Cd being measured in lunar samples for the first time by this method. While Cd was found to be heterogeneously distributed in some samples, Gd and Sm showed good agreement with previous measurements, except for sample 14163,848 where it was significantly lower.
Keywords: NEUTRON CAPTURE; MASS SPECTROSCOPY; ISOTOPE DILUTION; ENERGY SPECTRUM; MOON; CADMIUM; GADOLINIUM; SAMARIUM